Learning and Memory Processes Following Cochlear Implantation: The Missing Piece of the Puzzle - Pisoni, David B.; Kronenberger, William G.; Chandramouli, Suyog H.; Conway, Christopher M. (Frontiers in Psychology, 2016)
At the present time, there is no question that cochlear implants work and often work very well in quiet listening conditions for many profoundly deaf children and adults. The speech and language outcomes data published over the last two decades document quite extensively the clinically significant benefits of cochlear implants. Although there now is a large body of evidence supporting the "efficacy" of cochlear implants as a medical intervention for profound hearing loss in both children and adults, there still remain a number of challenging unresolved clinical and theoretical issues that deal with the "effectiveness" of cochlear implants in individual patients that have not yet been successfully resolved. In this paper, we review recent findings on learning and memory, two central topics in the field of cognition that have been seriously neglected in research on cochlear implants. Our research findings on sequence learning, memory and organization processes, and retrieval strategies used in verbal learning and memory of categorized word lists suggests that basic domain-general learning abilities may be the missing piece of the puzzle in terms of understanding the cognitive factors that underlie the enormous individual differences and variability routinely observed in speech and language outcomes following cochlear implantation.